Analisis Pengaruh Komunikasi Organisasi Dan Budaya Organisasi Terhadap Disiplin Kerja Dan Implikasinya Terhadap Kinerja Pegawai Humas Dan Protokol Sekretariat Daerah Kabupaten Paser - Yuli Rahmadhani; Abubakar Iskandar (Institut Pertanian Bogor, 2016)
Success or failure depends on the goals of the organization Public Relations employee performance. Initial observation showed that the performance of employees still lower. Because the purpose of this research is (1) Want to know the organization's communication to the discipline of work, (2) Describe the influence of organizational culture on work discipline, (3) to analyze the influence of organizational communication and organizational culture simultaneously to labor discipline, (4) Want to know the effect of organizational communication on performance, (5) to analyze the influence of organizational culture on performance, (6) to analyze the influence of organizational communication and organizational culture simultaneously on performance, and (7) Want to know the discipline of work on performance. The method used is quantitative and qualitative, while the location of the research is part of Public Relations and Protocol Meanwhile time study for six months .. sample was 35 people. The data collection technique is a literature study, observation, interviews, questionnaires. Data were analyzed through path analysis and content analysis. Research shows that the effect on the organization's communications work discipline by 0,024. The influence of organizational culture on work discipline at: 0,974. The influence of organizational communication and organizational culture on work discipline influence the organization's communication of 0,000 on the performance of 0,885, the influence of organizational culture on performance of 0,740. The influence of organizational communication and organizational culture obtained F value of 55 400 with a significance level of 0.000. Work Discipline influence on the performance of statistical calculations based on the total effect on the Performance Work Discipline variable through variable Organizational Communication and Cultural Organization that is equal to -107%. These values indicate that the Work Discipline can negatively affect employee performance. Work discipline employees not as expected so do not improve employee performance optimal.Key Words: Communication, Culture, Performance Discipline, Public Relations